2017
DOI: 10.1177/0969733017703696
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of organ donation in brain-dead patient's families: Ethical perspective

Abstract: Donor families experience different challenges which range from conflict and doubtfulness to confidence, satisfaction, and transcendence. Healthcare providers and organ procurers should not discontinue care and support provision to donor families after obtaining their consent to donate because the post-decision phase is also associated with different complexities and difficulties with which donor families may not be able to cope effectively. In order to help donor families achieve positive outcomes from the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 37 publications
0
30
0
4
Order By: Relevance
“…Knowing the deceased's prior wishes or having prior discussions about donation in the family was the most important factor that facilitated the decision and prevented family disagreement and instability in the decision (de Groot et al, 2012; Miller & Breakwell, 2018;Rodrigue et al, 2008;Sarti et al, 2018). Families' fears and suspicions about OD were other barriers to decision making; hence, distrust in the diagnosis of brain death and the OD process, fear of being responsible for death, being accused of selling organs, and fear of disfiguration of the deceased's body negatively affected the OD decision (Ahmadian et al, 2019;Huang et al, 2019;Podara et al, 2021;Ralph et al, 2014). The quality of the OD request had a significant impact on families' decision.…”
Section: Distrust Towardmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the deceased's prior wishes or having prior discussions about donation in the family was the most important factor that facilitated the decision and prevented family disagreement and instability in the decision (de Groot et al, 2012; Miller & Breakwell, 2018;Rodrigue et al, 2008;Sarti et al, 2018). Families' fears and suspicions about OD were other barriers to decision making; hence, distrust in the diagnosis of brain death and the OD process, fear of being responsible for death, being accused of selling organs, and fear of disfiguration of the deceased's body negatively affected the OD decision (Ahmadian et al, 2019;Huang et al, 2019;Podara et al, 2021;Ralph et al, 2014). The quality of the OD request had a significant impact on families' decision.…”
Section: Distrust Towardmentioning
confidence: 99%
“…
rgan transplantation is an effective procedure in saving the lives of patients with end-stage organ failure (López et al, 2018), which can lead to improving the recipients' quality of life (de Moraes et al, 2018); however, it remains limited because of the gap between organ access and the number of patients requiring it (López et al, 2018).The growing need for donor organs has become a major health concern in the world (Ahmadian et al, 2019). In April 2018, more than 114,000 people were on the waiting list for organ transplant in the United States whereas only 34,770 transplants were performed in 2017 (i.e., about 30% received the transplant).
…”
mentioning
confidence: 99%
“…Despair, hope, guilt, and grief were just some of the words used by relatives to describe their feelings. 12,14,15 Ahmadian, et al 16,17 published two studies in 2019, one looking at relatives' experiences during the organ donation process in Iran and a second looking at the period following the decision. The combined research showed a trajectory over time that was described as from conflict to confidence, satisfaction, and eventually transcendence.…”
Section: Emotional Aftermathmentioning
confidence: 99%
“…That research also identified three key aspects for next of kin: all wanted to receive news of the operation to retrieve organs if they were not present, all wanted news of successful transplantation, and to know how many there had been.10 In multiple studies, families described wanting to receive letters from the recipient. 13,14,17 Ahmadian, et al17 included one next of kin who not only wanted a letter but also was disappointed they were unable to meet the recipient.17 Additionally, Poppe, et al found that 72.9% would like a letter from the donor recipients. 13…”
Section: Providing Supportmentioning
confidence: 99%
“…In such cases, it would be important for clinicians to provide social and emotional support for families experiencing the organ donation process, and communicate sensitively when asking for consent. (14,15) An opt-out system would increase the number of organs collected for medical research or teaching purposes-when an organ is unsuitable for transplant or if a speci c tissue type of organ is desired for research. Organ use in research could contribute to providing vital information about the pathology of a disease; and assist in the development of more e cacious drugs with improved safety pro les, as they would be tried on a donated organ before risking the safety of a participant in a trial.…”
Section: Abstract -mentioning
confidence: 99%